Comparative leaf epidermis study in Habenaria spp. (Orchidaceae) from Thailand (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Muangsan N, Saensouk P, Chanokkhun T, Watthana S. 2022. Comparative leaf epidermis study in Habenaria spp. (Orchidaceae) from Thailand. Biodiversitas 23: 4159-4168. The variation of epidermal and stomatal characteristics could be used for plant classification, including orchids. This study aimed to investigate leaf epidermis characters of Habenaria from Thailand and focused on the H. rhodocheila group and related species. Fourteen accessions belonging to 10 species were studied and compared. Epidermal peels were taken from the upper and lower surfaces of the leaves and were observed under a light microscope. The stomata of all accessions studied were distributed only in the lower epidermis, where they were hypostomatic and anomocytic. The epidermal cell density showed significant differences between the two surface sides. The stomatal size is significantly different among all samples. The highest stomatal index was presented in H. rostrata and the lowest on H. rhodocheila (red). There is no gap variation of epidermis characteristics in H. rhodocheila and its closely related species. It is indicated that the leaf epidermal characters are the shared characters of the genus Habenaria from Thailand. H. rostrata has tentatively separated from other species based on epidermal anatomical characteristics.